2018
DOI: 10.1002/lt.25181
|View full text |Cite
|
Sign up to set email alerts
|

Low Preoperative Platelet Count Predicts Risk of Subclinical Posthepatectomy Liver Failure in Right Lobe Donors for Liver Transplantation

Abstract: Living donor right hepatectomy (LDRH) is a common procedure in adult-to-adult living donor liver transplantation, but it is associated with a higher risk of posthepatectomy liver failure (PHLF) compared with left hepatectomy because of a smaller remnant. We identified risk factors for PHLF and other complications in LDRH, verified the appropriateness of the criteria, and explored the possibility of adjusting the minimum remnant liver volume (RLV) based on individual risk. Between October 2005 and November 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…These results suggest that splenomegaly after donor surgery is not only a phenomenon of mere splenic enlargement, but indicates signs of portal hypertension while being subclinical. Predictably, PLT decrease was significantly greater in the right lobe donors than in the left lobe/lateral segment donors, reaffirming that living donor right hepatectomy in individuals with lower PLT levels should be carefully considered not only in terms of short‐term morbidity but also in terms of long‐term consequence. This supports our current policy to use left lobe grafts with priority …”
Section: Discussionmentioning
confidence: 66%
“…These results suggest that splenomegaly after donor surgery is not only a phenomenon of mere splenic enlargement, but indicates signs of portal hypertension while being subclinical. Predictably, PLT decrease was significantly greater in the right lobe donors than in the left lobe/lateral segment donors, reaffirming that living donor right hepatectomy in individuals with lower PLT levels should be carefully considered not only in terms of short‐term morbidity but also in terms of long‐term consequence. This supports our current policy to use left lobe grafts with priority …”
Section: Discussionmentioning
confidence: 66%
“…Screening of 1386 records and 43 full texts as well as addition of three articles identified from other sources led to three articles matching eligibility criteria (Figure 1). These three articles described retrospective cohort studies 8,14,15 . In these studies, a total of 1193 living donors underwent partial hepatectomy.…”
Section: Resultsmentioning
confidence: 99%
“…However, our review demonstrates that donor age does not confer an increased risk for postoperative complications, increased length of stay, or biochemical hepatic recovery. It is important to note that donor selection was exclusive to donors who age ≤ 65 years (with no comorbidity) in one study 14 with well-controlled hypertension without end-organ damage or other cardiovascular abnormalities were allowed to donate; an approach that is in line with the opinion of our expert panel. The findings of these studies are also in line with the recent observations in general population.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The remnant liver volume ratio, which was recommended to exceed the minimum of 30% to 35% for donor safety[ 54 ], is closely related to postoperative morbidity such as liver failure, and platelets have been highlighted as playing an important role in this condition. Yoshino et al [ 55 ] retrospectively collected data from 254 donors undergoing LDLT and showed that a lower preoperative platelet count was an independent risk factor for postoperative complications, such as bile leakage, subphrenic effusion, infectious ascites, postoperative anemia, and liver failure, after living donor hepatectomy. Emond et al [ 56 ] demonstrated that even in healthy donors, the fluctuation of platelet count within the normal range was negatively associated with potential portal hypertension and subclinical liver dysfunction, indicating that platelet count might serve as a surrogate marker to predict potential liver failure in healthy donors.…”
Section: Evidence From Clinical Studiesmentioning
confidence: 99%